2022
DOI: 10.1108/md-02-2022-0237
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of safety-based performance in construction projects with neutrosophic data envelopment analysis

Abstract: PurposeThe main purpose of this paper is to create a suitable structure based on neutrosophic numbers to evaluate the safety performance in construction projects in such a way that the shortcomings can be highlighted with the reasoned measurement and possible strategies can be recommended.Design/methodology/approachData envelopment analysis (DEA), which is a useful tool for performance appraisal, along with neutrosophic logic, which is one of the most complete tools for handling uncertainty phenomenon, has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…NN consists of a crisp parameter and a value with a literal indeterminacy parameter (I), and can explain the restricted confident and restricted indeterminate information using formula A 5 a þ bI. To evaluate the safety performance in building projects, Li et al (2023) suggested a framework based on the combination of data envelopment analysis (DEA) and NN to expose deficiencies with the rational measurement and recommend possible strategies. This hybrid model evaluates a new approach as an indicator of safety performance, and several units are compared.…”
Section: Published Researchmentioning
confidence: 99%
“…NN consists of a crisp parameter and a value with a literal indeterminacy parameter (I), and can explain the restricted confident and restricted indeterminate information using formula A 5 a þ bI. To evaluate the safety performance in building projects, Li et al (2023) suggested a framework based on the combination of data envelopment analysis (DEA) and NN to expose deficiencies with the rational measurement and recommend possible strategies. This hybrid model evaluates a new approach as an indicator of safety performance, and several units are compared.…”
Section: Published Researchmentioning
confidence: 99%
“…The new concepts of IVFNG are employed to find the best materials that are used for making dental implants in the case of smokers. There are many researchers developed and studied different types uncertainty sets and their application in Multi-Criteria Decision-Making (MCDM) (Duran et al, 2021;Ejegwa et al 2022;Mohanta et al, 2020;Li et al, 2022;Smarandache, 2020;Smarandache, 2022;Wang et al, 2022;Zhang et al, 2022). Mahesh et al (2022), made a comparative study Author Contributions: Conceptualization, S.B and F.S; methodology, S.B., M.T., and A.B; software, R.S.…”
Section: Proposed Ivfng Framework For Mcdm Problemmentioning
confidence: 99%
“…With the development of evaluation methods, some combinatorial evaluation methods based on fuzzy mathematics are applied more successfully [30][31][32]. This paper intends to combine the analytic hierarchy process, particle swarm optimization algorithm, and fuzzy mathematics comprehensive evaluation method, through the subjective and objective mutual combination of methods, a comprehensive evaluation of the comprehensive benefits of the land.…”
Section: Related Types Of Researchmentioning
confidence: 99%